Pengaruh Pendidikan, Pertumbuhan Penduduk, Dan Pengangguran Terhadap Persentase Penduduk Miskin Di Provinsi Bali - Indraswari, Dewa Ayu Putri; Budhi, Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700]DO - 10.24843/EEP.2022.v11.i09.p01, 2022)
Poverty is an absolute and relative condition that causes a person or group of people in an area to not have the ability to fulfill their basic needs according to certain values ??or norms that apply in society due to natural, cultural, or structural reasons. This study aims to analyze the effect of education, population growth, and unemployment simultaneously and partially on the percentage of poor people in Bali Province. This study uses secondary data from 2015-2019 using the SPSS program. The analysis technique used is multiple linear regression. The results show that partially, it is known that the education variable has a negative and significant effect, while the population growth and unemployment variables have a positive and significant effect on the percentage of poor people in Bali Province. Furthermore, it is known that the variables of education, population growth, and unemployment have a simultaneous and significant effect on the percentage of poor people in Bali Province.